2010
DOI: 10.1242/jeb.042994
|View full text |Cite
|
Sign up to set email alerts
|

‘It's hollow’: the function of pores within myoglobin

Abstract: SUMMARY Despite a century of research, the cellular function of myoglobin (Mb), the mechanism regulating oxygen (O2) transport in the cell and the structure–function relationship of Mb remain incompletely understood. In particular, the presence and function of pores within Mb have attracted much recent attention. These pores can bind to Xe as well as to other ligands. Indeed, recent cryogenic X-ray crystallographic studies using novel techniques have captured snapshots of carbon monoxide (CO) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 92 publications
1
50
0
Order By: Relevance
“…Within the Mb protein are several highly conserved hydrophobic cavities oxygen partial pressure (mmHg) (Fig. 5), including the heme pocket, the distal pocket (DP) and four additional pockets (Xe1-Xe4) (Tomita et al, 2010). A porphyrin ring is present within the heme pocket and is stabilized by hydrophobic interactions with nonpolar amino acids.…”
Section: Globin Form and Functionmentioning
confidence: 99%
“…Within the Mb protein are several highly conserved hydrophobic cavities oxygen partial pressure (mmHg) (Fig. 5), including the heme pocket, the distal pocket (DP) and four additional pockets (Xe1-Xe4) (Tomita et al, 2010). A porphyrin ring is present within the heme pocket and is stabilized by hydrophobic interactions with nonpolar amino acids.…”
Section: Globin Form and Functionmentioning
confidence: 99%
“…The presence and function of internal cavities in Mb have attracted much attention recently, in particular focused on swMb [22][23][24][25][26][27][36][37][38][39]. To provide cavity information for apMb, we analyzed the cavities in both close and open forms of apMb and compared to that in swMb with energy minimization and MD simulation.…”
Section: Internal Cavities Of Swmb and Apmbmentioning
confidence: 99%
“…More hydrophobic residues such as F28, F112 and F134 locate among the cavities in apMb, resulting in a lower connectivity of these cavities. These differences may be related to the ligand binding kinetics and migration pathways inside the protein [22][23][24][25][26][27][37][38][39].…”
Section: Internal Cavities Of Swmb and Apmbmentioning
confidence: 99%
“…[19][20][21][22] A number of computational studies have been reported on the diffusion of O 2 through intra-molecular tunnels. [22][23][24][25][26][27][28][29] One possible approach to investigate the transport of these types of molecules involves standard MD simulation of ligand diffusion, which ideally requires a large number of independent replicate runs of several ns to attain adequate sampling (flooding simulation). 19,22 A second approach involves the determination of the potential of mean force (PMF).…”
Section: Introductionmentioning
confidence: 99%